IDENTIFICATION OF HEAT SOURCE IN THE GEOTERMAL SYSTEM OF MOSSO VILLAGE, MUARA TAMI DISTRICT, JAYAPURA CITY USING THE GRAVITY METHOD - Alin Sharina Dwi Yampy (Papua Journal of Physics Education, 2026)
Kampung Mosso exhibits geothermal manifestations in the form of hot springs. One of the geothermal exploration methods is gravity anomaly analysis, which provides information about subsurface structures and rock density distribution. Through 3D modeling based on gravity data, subsurface geological structures can be interpreted to identify heat sources and the depth of geothermal reservoirs. Secondary data from GGM Plus is used as the source of gravity anomaly data. The data is then processed using Oasis Montaj for initial visualization and geophysical data processing, Surfer for interpolation and contour map generation, and Bloxer for 3D modeling of subsurface density distribution. The modeling process employs an inversion method, where an initial model is constructed and iterated until a final model with minimal error is obtained. This model is then analyzed to determine the subsurface structure and identify the heat source within the Kampung Mosso geothermal system. This study aims to develop a 3D model of subsurface structures based on gravity anomaly data, identify heat sources in the Kampung Mosso geothermal system based on the model, and determine the depth of the heat source. The results of this study are expected to illustrate the distribution of gravity anomalies in the Kampung Mosso hot spring area.